Types of Social Media Use and Digital Stress in Early Adolescence. (March 2023) - Winstone, Lizzy; Mars, Becky; Haworth, Claire M. A.; Kidger, Judi
Evidence on how different types of social media use contribute to digital stress in early adolescence is lacking. In-depth interviews were conducted with 24 13–14-year-olds. Interviews were transcribed verbatim, coded and thematically analysed. Themes were generated based on digital stressors specific to passive social media use (time-wasting and digital guilt, and exposure to harmful content); private social media communication (expectations of availability and unsolicited contact by strangers); and social media broadcasting (expectations of perfection and sexualisation, fear of negative evaluation and risks to privacy). Several digital stressors appeared pervasive in everyday social media use. Bolstering social and emotional resources offline and encouraging effective implementation of privacy settings may improve resilience against several sources of digital stress.